The Influence of Interactivity, Online Customer Reviews, and Trust on Shopee Live Streaming Users' Impulse buying - Masitoh, Martina Rahmawati; Wibowo, Hermansyah Andi; Prihatma, Gugup Tugi; Miharja, Dede Tory (GREENOMIKA, 2024)
The purpose of this study is to investigate the effect of interactivity, online customer reviews, trust on impulse buying in Shopee live streaming (Shopee Live) customers domiciled in Indonesia who have purchased on Shopee live at least 2 times. Our approach is a quantitative approach. This study uses a survey design by distributing questionnaires. The sampling technique used is purposive sampling. The number of samples used in this study is 155 samples. Data processing is carried out statistically by utilizing variance-based Structural Equation Modeling (PLS-SEM). Data processing is carried out with the help of SmartPLS ​​software ver. 3. The results of the study show that: (1) interactivity has a significant effect on impulse buying; (2) interactivity has a significant effect on trust; (3) online customer reviews have a significant effect on trust; (4) online customer reviews do not have a significant effect on impulse buying; (5) trust has a significant effect on impulse buying. The results of the study also show that there is an indirect effect, namely interactivity has a significant effect on impulse buying through trust and also online customer reviews have an indirect effect on impulse buying through trust.